Modeling, simulation, motion trajectory planning and nonlinear control in the joint space of the manipulator robot SCARA T3 401SS manufacturer Epson - Rossini, Flávio Luiz; Lima, Bruno Suracci de; Corrêa, Joao Henrique Dias; Lopes, João Marcos Pericaro; Barbosa, Reginaldo Ferreira De Sousa; Barrozo, Yuri Ruzzene (Seven Editora, 2023)
The paper proposed the mathematical modeling, trajectory planning, and nonlinear control of the SCARA T3 401SS manipulator robot from manufacturer Epson. The National Confederation of Industry (CNI) developed a survey on the results of companies that have adopted Industry 4.0 concepts, and the results were released in 2018, which extensively use robots in their manufacturing plants. In Brazil, there are about 1,595 units with robots installed. Thus, the static and dynamic models of the robot were developed, which were used to carry out the trajectory planning and the nonlinear control system partitioned based on a model in the joint space. From this proposal, the code was constructed in the MATLAB® software environment. Then, the simulation was performed and the numerical results were obtained, regarding the position, speed, and acceleration of the effector about the fixed base of the robot, in the context of static and dynamic modeling. Through the mathematical description and computer simulation, the results proved to be coherent and promising, which have the purpose of contributing to students and professionals in the area who seek temporal models and behaviors, to check, compare and implement new embedded technologies. As well as evaluate the best performance of the robotic system. DOI:https://doi.org/10.56238/devopinterscie-248